Guia para atendimento de enfermagem às vítimas de acidentes ofídicos no contexto hospitalar - Cunha, Naylanny Gonçalves Torres (Universidade do Vale do Rio dos Sinos, 2024)
Introduction: snakebites, also known as snakebite, are triggered by snakes that, when biting a victim, inoculate toxins that can cause local and/or systemic changes. These accidents, in Brazil, constitute a public health problem, given the frequency in which they occur, especially in rural areas, and the severity they can produce. Therefore, it is important that nursing professionals are prepared to deal with these situations. Objective: to develop a guide for nursing care for victims of snakebites in the hospital context. Method: methodological study carried out in two stages: 1st) bibliographic study; seeking to support the definition of content to be covered in the nursing guide; 2nd) preparation of the nursing guide. Results: in the bibliographic study, the following were selected for analysis: one book, two guides and six articles. Three chapters were extracted from the guides, originating from the Ministry of Health and the Health Department of the State of Ceará. The selected articles were published in Brazil, in the Virtual Health Library Portal (VHL) and Researchgate Portal databases. Content analysis was used to generate the categories: nursing care for victims of snakebites; care in administering serotherapy to victims of snakebites; flowchart of care for victims of snakebites. These three categories supported the content of the guide, which was composed of twenty-five pages and divided into seven chapters. Conclusion: the guide, as a product generated in this study, according to the Coordination for the Improvement of Higher Education Personnel (CAPES), considering the Technical and Technological production of the Nursing Area, is classified as a Manual or Protocol, has a potential impact, as it may contribute to supporting the standardization of the organization of care and nursing care for victims of snakebites in the hospital context. Furthermore, it can be replicated in other institutions in the region under study, helping to improve care.
Keywords: Animais venenosos; Cuidados de enfermagem; Mordedura de serpentes; Poisonous animals; Nursing care; Snake bites; ACCNPQ::Ciências da Saúde::Enfermagem